Odpowiedź :
Odpowiedź:
27^8 : 3^5 = (3³)^8 : 3^5 = 3^24 : 3^5 = 3^19
27^9 : 9^10 = (3³)^9 : (3³)^10 = 3^27 : 3^30 = 3^-3
7^5 * 5^7/35^5 = 7^5 * 5^7 : (5^5 * 7^5) = 5²
4^13 * 6^13 : 24^13 = (4 * 6)^13/24^13 = 24^13 : 24^13 = 24^0 = 1
Szczegółowe wyjaśnienie:
Odpowiedź:
27^8 : 3^5 =3 ^ x
(3^3)^8 : 3^5 =3^x
3^24 : 3^5 = 3^19
x = 19
27^9 : 9^10 = 3^y
(3^3)^9 : (3^2)^10 = 3^y
3^27 : 3^20 = 3^7
y=7
7^5*5^7/ 35^5 = z
7^5*5^7/ 7^5 * 5^5 = z
5^2 = z
4^13* 6^13/ 24^13 =k
24^13/ 24^13 = k
1 = k
Szczegółowe wyjaśnienie: